Determinants of mammography screening behavior in Iranian women: A population-based study - Moodi, Mitra (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Breast cancer remains a substantial health concern in Iran due to delay and late stage at diagnosis and treatment. Despite the potential benefits of mammography screening for early detection of breast cancer, the performance of this screening among Iranian women is low. For planning appropriate intervention, this study was carried out to identify mammography rates and explore determinants of mammography screening behavior in females of Isfahan, Iran. MATERIALS AND METHODS: In this population-based study, 384 women of 40 years and older were interviewed by telephone. The Farsi version of Champion's Health Belief Model scale (CHBMS) was used to examine factors associated with mammography screening. The obtained data were analyzed by SPSS (version 16.0) using statistical Chi-square, Fisher Exact test, t-test and multiple logistic regression model to identify the importance rate of socio-demographic and Health Belief Model (HBM) variables to predict mammography screening behavior. In all of tests, the level of significant was considered a = 0.05. RESULTS: Mean age ± SD of women was 52.24 ± 8.2 years. Of the 384 participants, 44.3% reported at least one mammogram in their lifetime. Logistic regression analysis indicated that women were more likely to have mammography if they heard/read about breast cancer (OR = 4.17, 95% CI 2.09, 8.34), menopause in lower age (OR = 0.2, 95% CI 0.87, 0.99) and history of breast problem (OR = 0.9, 95% CI 0.12, 0.32). Also, women who perceived more benefits of mammography (OR = 1.84, 95% CI 1.63, 2.09), fewer barriers of mammography (OR = 0.91, 95% CI 0.86, 0.96) and had more motivation for health (OR = 0.94, 95% CI 0.89, 1) were more likely to have mammography. CONCLUSION: The findings indicated that the rate of mammography screening among women in Isfahan province is low and highlights the need for developing a comprehensive national breast cancer control program, which should be considered as the first priority for healthcare providers. Also, identification of these factors can help to design an appropriate educational intervention that focuses on benefits of mammography screening, decreasing changeable barriers, improving access to mammography, increasing health motivation, promoting perceived self-efficacy and mammography adherence.